(untitled) (International Journal of Language, Literacy and Translation, 2025)
The utilization of languages spoken by minority groups is a frequently observed topic in the field of linguistic landscape research. Based on empirical data, this paper examines the linguistic landscapes of two historic towns, Dayan and Shuhe, in Lijiang's Old Town to delve into the language use situation, especially the status of ethnic minority languages in a multi-ethnic area in China. The two old towns constitute the major administrative area in the Old Town of Lijiang, a renowned World Heritage Cultural site and a 5A-level tourism spot in China. The research concentrates on the languages displayed in the public signs in the selected areas to unveil the languages used and their relative weights in top-down and bottom-up flows. A quantitative method was applied by collecting digital photos to calculate the proportions and percentages of the languages used, and observations were done to recognize the preferred language in bilingual and multilingual signs. It is found that Dayan Old Town exhibits a greater degree of multilingualism than that of Shuhe Old Town with a more extensive use of multiple languages. The analysis of the linguistic landscape shows that Chinese enjoy absolute visibility among all the languages used, and Dongba scripts function as a cultural icon for eye-catching by featuring it at the top of the order of appearance among other languages in bottom-up signs, albeit not as prominently as Chinese. Besides, the appearance of English as a global language is prevalent in regional linguistic environments as it is encouraged to be seen in the top-down multilinguist signs. The language use situation in the selected streets will shed light on future research on the linguistic landscape in multi-ethnic areas in rural China, especially the cities suspended by tourism avenues.